PERAN PENGAWASAN KEPALA SEKOLAH DALAM SUPERVISI PENDIDIKAN: STUDI KASUS PADA KINERJA GURU - Nabilla, Shalsa; Sari, Gita Puspita; Kinanthi, Ajeng Cindy; Selviana, Selviana; Panjaitan, Keiza; Wijaya, Hansein Arif (Universitas Riau, 2023)
The purpose of this study is to explain the role of principal supervisors in educational supervision: focusing on teacher performance. This research was conducted through a qualitative approach and used a descriptive qualitative research type. A deputy principal was the respondent of this study. Interviews, documentation and observation were used to collect data. Analyzing the data using field analysis based on the Miles and Huberman model, which goes through three steps: data reduction, data presentation and conclusion drawing. The results show that principals have a very important role in managing and improving the quality of education in schools and the use of the Electronic Performance (E-Kinerja) application strengthens supervision of teacher and staff performance. Despite identifying some obstacles, such as teachers' tardiness and the low attendance of administrative staff, principals take a solutive approach.